(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
The current research seeks to determine the readiness of organizations to apply the (DMAIC) methodology, a diagnostic and analytical study of the opinions of a sample of employees in the General Company for Electricity Distribution in the North, to establish an advanced industrial environment capable of providing services that meet the needs of customers in terms of distinctive quality and cost, in addition to securing a competitive advantage that gives it the ability to confront competing organizations by relying on production systems of superior quality, including the (DMAIC) methodology. The research problem was based on the following questions: - To what extent do managers in the company under study know the concept of the (DMAIC) methodology? - Do managers in the company under study seek to apply the (DMAIC) methodology? - What are the most appropriate applications for implementation in the company under study? The Research Reached a Set of Conclusions, the Most Important of Which are: - There is a readiness in the company under study to establish the (DMAIC) methodology. - There is great importance in applying the (DMAIC) methodology in the company under study. In Light of the Previous Conclusions, Several Proposals Were Presented, the Most Prominent of Which are: - The interest of the management of the company under study in the applications of the (DMAIC) methodology is increasing. - Determining a timetable for the tasks through which services are produced in the company under study.